FAKTOR-FAKTOR YANG MEMENGARUHI PERILAKU SEKSUAL NARAPIDANA REMAJA PRIA DI LEMBAGA PEMASYARAKATAN KELAS II B BALIGE KABUPATEN TOBA SAMOSIR TAHUN 2012 - Nani A K Siregar; Asfriyati .; Abdul Jalil Amri Arma (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Adolescents are those who are experiencing changes from childhood into adulthood. These changes include changes in the physical and emotional changes. Juvenile inmates is a group of teenagers who have complex problems, in addition to have committed the crime, followed by poor sexual acts plus more are in prison who daily interact with other youth inmates that will influence each other.This study aims to determine the factors that influence sexual behavior in male adolescent inmates Penitentiary class IIB Balige Toba Samosir regency in 2012. This research is a descriptive-analytic. Sampling was done by sampling with a total sample size of 30 people. Data were analyzed by Chi Square test with α 0.05. The results using logistic regression showed that the significant variables, namely knowledge (p = 0.038) and attitude (p = 0.022). Predictors forecast the probability 1, that the adolescent male inmates who have less knowledge of both affected by unfavorable attitude has a probability of sexual behavior at 5.46%, while probability prediction with predictor 0 was 91,21%.Teens who are in prison have limited knowledge about sexual problems and many have done just that deviant sexual behavior. Therefore to the prison to conduct outreach efforts on adolescent reproductive health issues and sexually transmitted diseases to the inmates teenage boys. Keywords: Adolescent Sexual Behavior-Male Inmates